A new housing group for sub-residential area in Samarkand: a morphological comparison - Onder, DE (ELSEVIER SCI LTD, 2002)
In this study, information related to housing in Samarkand is provided and the spatial organisation of Samarkand houses is analysed by using the gamma analysis method in order to establish and define their patterning. After examining the existing housing pattern, a proposal is offered for the housing group where families can engage in guest-housing activity; this has been designed. by using the data obtained from the surveys and interviews conducted in situ, and has been evaluated by using the same space syntax method. Finally, the similarities and differences between the traditional housing and the proposed housing are pointed out. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: gamma analysis; traditional houses in Samarkand; proposed houses; morphological comparison; Urban Studies